Does Being Visible Mean Being Trusted? The Role of Digital Presence and Online Reviews in Generation Z's Wedding Service Selection - Naila Dwi Rizqi Nur’aini; Taufan Ali Achmadi (Jurnal Mantik, 2026)
Consumer decisions regarding wedding beauty services are increasingly influenced by digital information, particularly among Generation Z. Although previous studies have examined e-WOM, online reviews, digital presence, and consumer trust, limited research has simultaneously investigated digital presence and online reviews in building consumer trust within the wedding beauty service industry. This study aims to examine the influence of digital presence and online reviews on consumer trust and the subsequent influence of consumer trust on Generation Z’s service selection decisions. The novelty lies in integrating digital presence and online reviews into a single model within the relatively underexplored context of wedding beauty services. A quantitative explanatory approach was employed using a survey of Generation Z respondents aged 18–27 years who actively use digital platforms and have searched for or considered wedding beauty services. Respondents were selected through purposive sampling. Data were collected using a structured five-point Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results show that digital presence has a positive and significant effect on consumer trust (? = 0.493; p < 0.001), while online reviews also have a positive and significant effect on consumer trust (? = 0.457; p < 0.001). Consumer trust positively and significantly influences service selection (? = 0.781; p < 0.001). Theoretically, this study contributes to digital consumer behavior research by demonstrating the complementary roles of digital presence and online reviews in forming consumer trust. Practically, wedding beauty service providers should strengthen visual quality, content consistency, digital interaction, and credible online reviews to build trust and attract Generation Z. Future research should examine perceived authenticity, review credibility, influencer trust, and AI-generated reviews